2020
DOI: 10.3390/ijms21176084
|View full text |Cite
|
Sign up to set email alerts
|

Improved Autophagic Flux in Escapers from Doxorubicin-Induced Senescence/Polyploidy of Breast Cancer Cells

Abstract: The induction of senescence/polyploidization and their role in cancer recurrence is still a poorly explored issue. We showed that MDA-MB-231 and MCF-7 breast cancer cells underwent reversible senescence/polyploidization upon pulse treatment with doxorubicin (dox). Subsequently, senescent/polyploid cells produced progeny (escapers) that possessed the same amount of DNA as parental cells. In a dox-induced senescence/polyploidization state, the accumulation of autophagy protein markers, such as LC3B II and p62/SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 76 publications
3
19
0
Order By: Relevance
“…Indeed, the presence of lipid droplets is thought to be part of stress response to treatments, regulation of proliferation, migration and survival of cancer cells [ 86 ]. The additional presence of a great number of autophagic vacuoles in the cytoplasm indicates that Dox induced autophagy in the MDA-MB-231 cell line, which agrees with a previous report [ 87 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the presence of lipid droplets is thought to be part of stress response to treatments, regulation of proliferation, migration and survival of cancer cells [ 86 ]. The additional presence of a great number of autophagic vacuoles in the cytoplasm indicates that Dox induced autophagy in the MDA-MB-231 cell line, which agrees with a previous report [ 87 ].…”
Section: Discussionsupporting
confidence: 92%
“…Even though most TIS/TIP cells remain senescent for several weeks or ultimately die, several studies indicated that this process is reversible and that polyploid cancer cells could depolyploidize (also termed “neosis” [ 129 , 131 ]). The reversibility of TIS/TIP-mediated senescence leads to regained proliferative capacity of mononucleated progenies [ 123 , 126 , 128 , 129 , 132 ] similar to previously described rejuvenation by retrodifferentiation [ 133 , 134 , 135 ].…”
Section: Therapeutic and Clinical Consequences Of Cancer-cell Fusionsupporting
confidence: 80%
“…Several studies suggested that cancer cells could escape from chemotherapeutic- or radiation-induced DNA damage by developing therapy-induced senescence (TIS). This could be further associated with therapy-induced polyploidization (TIP) resulting in the formation of multinucleated polyploid giant cells carrying ten or more subnuclei and micronuclei [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Kaur and colleagues observed the origin of senescent multinucleated and giant cells after radiation and assumed that such polyploid cells were formed through radiation-induced homotypic cell fusions [ 130 ].…”
Section: Therapeutic and Clinical Consequences Of Cancer-cell Fusionmentioning
confidence: 99%
“…5A). As reference compound, we used doxorubicin previously described to induce senescence in breast cancer cells (24). The observed effects were similar to those elicited by doxorubicin.…”
Section: Induction Of Senescence In Breast Cancer Cellsmentioning
confidence: 89%